isk of malnutrition and oral nutritional support in a cohort of hospital inpatients - Pilar Martínez-Matsumoto (Revista Española de Nutrición Humana y Dietética, 2022)
Introduction: The disease-related malnutrition is considered a serious problem since it is strongly related to higher mortality rates, longer hospital stays, and increased costs for medical care.  A highly associated risk factor has been the decreased oral intake during the hospital stay; however, the use of oral nutritional supplements allows to heal the malnutrition burden having positive results.